Developing English Lesson Plans Based on Discovery Learning in Teaching Descriptive Text for the First Year Students of SMP - Fadhliani, Hamidina; Witri, Gustimal (Proceedings of the UR International Conference on Educational Sciences, 2018)
This research is aimed to develop Englishlesson plans based on discovery learning (one of learning models suggested in the 2013 Curriculum) and to find out the validity level of developing English lesson plans based on discovery learning in teaching descriptive text for the first year students of SMP. The research design is Research & Development (R&D) applied 4D model byThiagarajan (1974). To develop English lesson plans, there were three stages involve in this research, (a) define stage that is done to set and define the product development requirements, (b) design stage that is done to plan the draft of lesson plan and arranged it into the format and (c) develop stage that is done to modify and validate the lesson plan. In order to find out the validity level of developing English lesson plans, the data were collected using validation sheet of lesson plan validated by experts. Based on data analysis result, the validation score of lesson plan is 90.91%. The result showed that English lesson plans were very valid and can be implemented in a classroom.